2013
DOI: 10.1002/stem.1518
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of SOX2 in Cell Proliferation and Survival and Its Crosstalk with Oncogenic Signaling in Lung Cancer

Abstract: Tumor cells have long been observed to share several biological characteristics with normal stem/progenitor cells; however, the oncogenic mechanisms underlying the lung stem/progenitor cell signaling remain elusive. Here, we report that SOX2, a self-renewal factor in lung stem/progenitor cells, is highly expressed in a subclass of lung cancer cells, the proliferation, survival, and chemoresistance of which are dependent on SOX2 signaling. Overexpression of SOX2 promotes oncogenic phenotypes in lung cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
99
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(114 citation statements)
references
References 32 publications
13
99
1
1
Order By: Relevance
“…Functional analyses by gene knockdown and a chemical inhibitor revealed that ALDH and SOX2 are essential for the proliferation of ovarian CSCs. Of note, both ALDH1A and SOX2 expression contribute to chemo-resistance of ovarian cancer cell lines (35,(43)(44)(45). Therefore, SOX2 and ALDH may mediate its capability to confer chemo-resistance to ovarian CSCs as well as stem cell-related features.…”
Section: Discussionmentioning
confidence: 99%
“…Functional analyses by gene knockdown and a chemical inhibitor revealed that ALDH and SOX2 are essential for the proliferation of ovarian CSCs. Of note, both ALDH1A and SOX2 expression contribute to chemo-resistance of ovarian cancer cell lines (35,(43)(44)(45). Therefore, SOX2 and ALDH may mediate its capability to confer chemo-resistance to ovarian CSCs as well as stem cell-related features.…”
Section: Discussionmentioning
confidence: 99%
“…In lung cancer, SOX2 could regulate cancer cells apoptosis through MAP4K4-Survivin signaling pathway [27]. The emerging role of SOX2 in cell proliferation and survival by eliciting oncogenic EGFR and BCL2L1 signaling was identified as a prognosis marker and a therapeutic target [28]. Wnt signaling substantially could impact NSCLC tumorigenesis, prognosis, and resistance to therapy [29].…”
Section: Discussionmentioning
confidence: 99%
“…In various cancers, SOX2 has been indentified to promote proliferation and invasion [16,17]. Here, we explored whether the functional effect of miR-638 on NSCLC cell lines was dependent on SOX2.…”
Section: Silencing Of Sox2 By Sirna Partially Abolished the Enhancemementioning
confidence: 99%
“…Tissue sections were stained overnight at 4 °C with each CSLC marker anti-human antibody (Table 1). We used seven markers that have been reported to be CSLC markers for lung or other solid malignant tumors (Caveolin, Notch, CD44, CD166, SOX2, Aldehyde dehydrogenase 1 [ALDH1], and Musashi1) (Chou et al 2013;Fischer et al 2011;Jiang et al 2009;Kuang et al 2013;Leung et al 2010;Palaniyandi et al 2012;Zhang et al 2012). The slides were subsequently incubated with EnVision™ (DAKO, Glostrup, Denmark) for 1 h at room temperature, and the color reaction developed.…”
Section: Immunohistochemical Analyses Evaluation and Scoringmentioning
confidence: 99%